2010
DOI: 10.1007/s11581-010-0442-1
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a nanoparticle TiO2 photoelectrochemical cell utilizing a solid polymeric electrolyte of PAN–PC–LiClO4

Abstract: A nanoparticle TiO 2 solid-state photoelectrochemical cell utilizing as a solid electrolyte of poly (acrylonitrile)-propylene-carbonate-lithium perchlorate (PAN-PC-LiClO 4 ) has been fabricated. The performance of the device has been tested in the dark and under illumination of 100-mW cm −2 light. A nanoparticle TiO 2 film was deposited onto indium tin oxide-covered glass substrate by controlled hydrolysis technique assisted with spin-coating technique. The average grain size for the TiO 2 film is 76 nm. LiClO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…They consist of a variety of classical polymeric materials from synthetics polymer and its blends to bio-based polymer. Namely, PEO (Ren et al, 2002), poly (methyl methacrylate) (PMMA) (Lee et al, 2010e;Yang et al, 2008), polyethylene glycol (PEG) (Joseph et al, 2006), poly(ethylene glycol) methyl ether methacrylate (PEGMA) (Bella et al, 2013a(Bella et al, , 2013b, polyacrylonitrile (PAN) (Taslim et al, 2010;Rika et al, 2009;Rahman et al, 2010), poly(vinyl chloride) (PVC) (Rahman et al, 2004(Rahman et al, , 2007, and poly(vinylidene fluoride-co-hexafluoropropylene) (PVdF-HFP) Lee et al, 2008b;Priya et al, 2008;Noor et al, 2014). To date, polysaccharides and modified polysaccharides based materials such as chitosan (Buraidah et al, 2010), cellulose (Rudhziah et al, 2015) and carrageenan (Bella et al, 2015) received the attention due to their higher ionic conductivities at room temperature.…”
Section: Polymer Electrolytementioning
confidence: 99%
“…They consist of a variety of classical polymeric materials from synthetics polymer and its blends to bio-based polymer. Namely, PEO (Ren et al, 2002), poly (methyl methacrylate) (PMMA) (Lee et al, 2010e;Yang et al, 2008), polyethylene glycol (PEG) (Joseph et al, 2006), poly(ethylene glycol) methyl ether methacrylate (PEGMA) (Bella et al, 2013a(Bella et al, , 2013b, polyacrylonitrile (PAN) (Taslim et al, 2010;Rika et al, 2009;Rahman et al, 2010), poly(vinyl chloride) (PVC) (Rahman et al, 2004(Rahman et al, , 2007, and poly(vinylidene fluoride-co-hexafluoropropylene) (PVdF-HFP) Lee et al, 2008b;Priya et al, 2008;Noor et al, 2014). To date, polysaccharides and modified polysaccharides based materials such as chitosan (Buraidah et al, 2010), cellulose (Rudhziah et al, 2015) and carrageenan (Bella et al, 2015) received the attention due to their higher ionic conductivities at room temperature.…”
Section: Polymer Electrolytementioning
confidence: 99%
“…Compared to liquid electrolytes, polymeric electrolytes have been widely considered as promising solid electrolytes, and are extensively investigated for their application for emerging flexible lithium secondary batteries as they offer several advantages over liquid electrolytes and inorganic solid electrolytes. [8][9][10] In addition to resolving the leakage issues while preserving decent ionic conductivities, the additional benefits of using polymeric electrolytes arise from the enhanced resistance to variations in the volume of electrodes during the charge-discharge process, improved safety features, high flexibility and easy processability. 11,12 Pioneering work by Wright and colleagues in 1973 on poly(ethylene oxide) (PEO) polymer electrolyte doped by alkali metal salt escalated the intensive competition between battery industries over the last two decades with new entrants of electrolytic materials and huge discoveries with related publications.…”
Section: Introductionmentioning
confidence: 99%
“…To enhance the energy density, efforts to find a sustainable and safer electrolyte material have been under active research. Compared to liquid electrolytes, polymeric electrolytes have been widely considered as promising solid electrolytes, and are extensively investigated for their application for emerging flexible lithium secondary batteries as they offer several advantages over liquid electrolytes and inorganic solid electrolytes . In addition to resolving the leakage issues while preserving decent ionic conductivities, the additional benefits of using polymeric electrolytes arise from the enhanced resistance to variations in the volume of electrodes during the charge–discharge process, improved safety features, high flexibility and easy processability .…”
Section: Introductionmentioning
confidence: 99%
“…In this context, poly­(ethylene oxide) (PEO)-based solid polymer electrolytes (SPEs) were initially reported by Wright and co-workers in 1973, and more recently, they have been considered as promising solid electrolytes for LIBs owing to their high thermal and electrochemical stabilities, their high ionic conductivities at high temperatures, their excellent interface stabilities, and their good safety profiles. , However, owing to the high crystallinity of PEO polymers, PEO-based SPEs have low ionic conductivities compared to liquid electrolytes. To date, the majority of approaches have aimed at increasing the ionic conductivity and improving the stability profile at high voltages involves modifying the PEOs with different monomers or adding organic plasticizers and inorganic nanoparticles. Moreover, previous studies reported the development of semi-interpenetrating polymer networks (semi-IPNs) with enhanced ionic conductivities, wherein these semi-IPNs incorporate a mechanically stable polymer network as well as a low molecular weight PEO polymer as a Li-ion conductor …”
Section: Introductionmentioning
confidence: 99%